2020
DOI: 10.1101/2020.03.31.20048579
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Blood glucose levels in elderly subjects with type 2 diabetes during COVID-19 outbreak: a retrospective study in a single center

Abstract: Aims: Ideal glycemic control is of great importance for diabetic patients during public health emergencies of infectious diseases as long-term hyperglycemic are not only associated with chronic complications but also vital drivers of common and life-threatening infections. The present study was designed to investigate the changes of blood glucose levels in elderly subjects with type 2 diabetes(T2D) during COVID-19 outbreak. Methods: This retrospective study focused on the T2D outpatients at Fujian Provincial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 22 publications
3
34
1
3
Order By: Relevance
“…The disease course in patients with COVID-19 can be perturbed by diabetes mellitus in two ways. On the one hand, diabetes is a risk factor for severe disease 3,[16][17][18][19][20][21][22] and, on the other, SARS-CoV-2 infection has been associated with altered glucose metabolism 3,16,24,29 . Specifically, ketosis and ketoacidosis were observed during and after SARS-CoV-2 infection, both being at least indirect clinical indicators of a lack of insulin due to β-cell loss or malfunction 18,[25][26][27][28][29][30] .…”
Section: Discussionmentioning
confidence: 99%
“…The disease course in patients with COVID-19 can be perturbed by diabetes mellitus in two ways. On the one hand, diabetes is a risk factor for severe disease 3,[16][17][18][19][20][21][22] and, on the other, SARS-CoV-2 infection has been associated with altered glucose metabolism 3,16,24,29 . Specifically, ketosis and ketoacidosis were observed during and after SARS-CoV-2 infection, both being at least indirect clinical indicators of a lack of insulin due to β-cell loss or malfunction 18,[25][26][27][28][29][30] .…”
Section: Discussionmentioning
confidence: 99%
“…In turn, the presence of increased fasting blood glucose level > 126 mg/dl during the SARS infection was correlated with the increase in risk of death more than threefold [ 50 ]. The population particularly affected by the COVID-19 hyperglycemia are older people as demonstrated by Xue et al [ 51 ] as it seems that this population has an increased risk of hyperglycemia occurrence overall. Interestingly, a meta-analysis by Miller et al [ 52 ] revealed that the prevalence of diabetes increases the mortality, while comorbidities do not affect the overall number of deaths.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that infected elderly with diabetes had an elevated fasting blood glucose as opposed to their HbA1C which remained stable [66]. However, during the acute phase of the COVID-19 infection it is essential that strict glucose control is maintained to prevent the occurrence of complications [66,67].…”
Section: Glycemic Controlmentioning
confidence: 99%